Consumer specialization and the Romantic transformation of the British Grand Tour of Europe - Andreas Chai (Max Planck Institute of Economics, 2010)
This paper posits that significant changes in 19th century British recreational travel patterns resulted from a change in the manner in which tourists used entertaining stimuli in order to attain pleasure. Consumers no longer merely viewed arousing stimuli, but attempted to use them to produce emotional states of being which they could partially modify to intensify pleasurable feelings (Damasio 2003). The impetus for this modification stemmed from an increasing awareness that emotional responses could be to some degree self-cultivated, as embodied in the Romantic ethos that become popular at the time via the emergence of the paperback novel and magazine industry (Campbell 1987). By learning how to manipulate and modify mental images in a way that may not necessarily correspond with objective reality, Romantic tourists learned to elicit pleasure through engaging of their imagination. Such a change in the mode of pleasure seeking had important long run economic consequences for tourist regions throughout the European continent.
urn:nbn:de:gbv:27-20110628-134236-9
Keywords: D11; D13; O12; O40; 330; Consumer specialization; Emotions; Tourism; Romanticism; Konsumentenverhalten; Emotion; Urlaubsverhalten; Tourismus; Romantik; Großbritannien